Melting Pots & Mosaics Children of Immigrants in US-American Literature - Heinze, Rüdiger (American Culture Studies, 2018)
In the past decades, children of immigrants have drawn increased attention not only in press and media, but also in a number of academic fields, among them sociology, history, or ethnology. Surprisingly, literary and cultural studies have been somewhat more reluctant to approach the topic. While there is work on individual authors or, at the very most, particular ethnic groups, comparative approaches are rare. This monograph aims to amend this. It provides an extensive discussion of US-American literature about children of immigrants, comparing different authors, different ethnic groups and different literary and historical contexts.